An Industrial systems design study on MAC Farms - Buenaventura, Luis R. III.; Causapin, Mark Gabriel A.; So, Sheryl Lyn M.; Terrel, Joseph L. (Diliman, Quezon City College of Engineering, 2002)
The egg industry plays an important part in the Philippine economy. It produces employment and is a source of cheaper food for many Filipinos. It is considered a major global industry because of its large magnitude in terms of total population and capital expenditures. MAC Farms is a medium sized poultry in San Jose, Batangas. It is located in an area considered to be the "egg-basket" of the Philippines because it produces the largest percentage of the total consumed eggs every year. To stay competitive, it must recognize the sustainability of its business. Sustainability would encompass economic and environmental strategies that would guarantee survival in the short and long term horizons. Sustainability is not an idea that can be separated from other methodologies. It is a point of view that considers the welfare of future generations. This view means considering a system's affect on the environment and in turn, the ripple consequences which would eventually shape the direction of the company. In this context, the group investigated the problem or improvement areas of MAC Farms and assessed its economic and ecological impact. Weaknesses were discovered through observation and were then used for the SWOT analysis. The main issues which were deterrent to the company's growth were the underutilization of resources, inefficiencies in handling and transportation of eggs, lack of clear waste management and maintenance policies, and inadequacy of sales activities. Their resources include land, man-hours and machine-hours. Utilizing these excesses would be beneficial for the company. Improving on handling and egg transport would also increase company profitability by decreasing the number of cracked eggs. Lastly, the group found that important policies and sales activities are required to make MAC Farms competitive. With these weaknesses, the group proposed the reduction of cracked eggs by implementing a better egg handling system. Furthermore, it suggests doubling the production in five years and forward integrating by setting up retail stores. To augment to its profits and improve waste management, it designed a program wherein chicken manure would be utilized as fertilizer for tilapia fisheries or other crops. All of these recommendations were designed with economic and environmental sustainability in mind.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: MAC Farms; Egg trade; Poultry; System design